"It All Depends": Patient and Decision Partner Experiences in Cancer Clinical Trial Decision-Making. (May 2022) - Gray, Tamryn F.; Allgood, Sarah J.; Nolan, Marie T.; Gallo, Joseph J.; Han, Hae-Ra; Clayman, Marla L.; Budhathoki, Chakra; Lansey, Dina G.; Wenzel, Jennifer
While the supporting role of families and friends has been widely recognized in cancer care, little data exist on how they influence patients' decisions regarding clinical trial participation, accounting for patients' decisional preferences. The goal of our study was to examine the process of clinical trial decision-making from the perspective of adults with cancer and their decision partners. Semi-structured interviews were conducted with 12 patients and 12 decision partners—family and friends engaged in the medical decision-making. Themes included: (1) having the ability and confidence to make decisions; (2) gaining insight about clinical trials; (3) trusting someone in the process; and (4) realizing readiness and context. Our findings will enhance understanding of how patients make clinical trial decisions based on decisional preferences from the perspectives of patients and decision partners. The findings may also help to increase clinician awareness and inclusion of decision partners in conversations regarding clinical trials.